Analysis of the Impact of Digitization of Islamic Banking For Small and Medium Enterprises (SMEs) in Indonesia - Juwita Anggraini; Maya Panorama; Desi Handayani (Journal of International Conference Proceedings (JICP), 2019)
Islamic banking is one of the economic sectors that becomes the wheel of rotation of funds in a country that must develop and follow market. The application of financial technology to improve the efficiency of operational activities and the quality of bank services to its customers, because the utilization of financial technology is in line with the growing community needs for online-based financial services and the use of internet media for digital data. The rapid growth of technology and digital development has brought about business changes. If two decades ago financial technology innovations were still centered on internal banking, nowadays technological innovations are also reaching the customers or consumers. The question that arises is how much digital finance can be used by people who are not bankable (lower class society) whose transaction rates are small, who have low income, the distance to remote bank locations, information on banking is limited. What is the impact of digital finance on SME businesses.